Animasi Cerita Wayang Sebagai Media Pembelajaran Bahasa Jawa - Aji, Gilang Baskoro; Waluyo, Retno (Journal of Computer Science and Engineering (JCSE), 2021)
Abstract: Javanese culture is one of the cultures that existed in Indonesia. One of the many Javanese culture is a puppet. The role of Education in preserving the Puppet that is by implementing subject puppet stories Junior High School  syllabus in subjects of the Java language. Animated puppet stories "Drona Rangsang" is an animation that was created as a means of information learning more innovative and interesting. The idea of establishing this animated arise as solutions of problems faced by teachers of subjects Language Java SMP Negeri 2 Binangun, where in the delivery of the material teachers have difficulty because of the lack of interest and the interest of students towards subjects. This animation has been applied and used in SMP Negeri 2 Binangun in the process of teaching and learning. In making this animation method using MDLC (Multimedia Development Live Cycle) using the 6 (six) in the form of concept system development phase, designing, gathering materials, manufacturing, testing and distribution. The main software used to manipulate this animations are Proffesional Adobe Flash CS6. From the results of testing conducted through interviews with the Java language teachers claimed that animation is in compliance and can be used as well as the questionnaire against the 30 students produced a formula index of 83.50% strongly agree with categories. The conclusion of this animation is the process of learning students can be more interesting and full potential.Abstrak: Kebudayaan jawa merupakan salah satu kebudayaan yang ada di Indonesia. Salah satu dari sekian banyak kebudayaan Jawa adalah kesenian Wayang. Peran Dinas Pendidikan dalam melestarikan Kesenian Wayang yaitu dengan diterapkannya pokok bahasan cerita perwayangan pada silabus SMP mata pelajaran Bahasa Jawa. Animasi cerita wayang “Drona Rangsang” adalah suatu animasi yang dibuat sebagai sarana informasi pembelajaran yang lebih inovatif dan menarik. Gagasan dibuatnya animasi ini timbul sebagai solusi dari permasalahan yang dihadapi oleh guru mata pelajaran Bahasa Jawa SMP Negeri 02 Binangun, dimana dalam penyampaian materi guru mengalami kesulitan karena kurangnya minat dan ketertarikan siswa terhadap mata pelajaran. Animasi ini telah diterapkan dan digunakan di SMP Negeri 02 Binangun dalam proses belajar mengajar. Dalam pembuatannya animasi ini menggunakan metode MDLC (Multimedia Development Live Cycle) yang menggunakan 6 (enam) tahap pengembangan sistem berupa pengonsepan, perancangan, pengumpulan bahan, pembuatan, pengujian dan pendistribusian. Perangkat lunak utama yang digunakan untuk mengolah animasi ini adalah Adobe Flash Proffesional CS6. Dari hasil testing yang dilakukan melalui wawancara dengan guru Bahasa Jawa menyatakan bahwa animasi sudah sesuai dan dapat digunakan serta kuesioner terhadap 30 siswa dihasilkan rumus index sebesar 83,50% dengan kategori sangat setuju. Kesimpulan yang diperoleh dari animasi ini adalah proses belajar siswa dapat lebih menarik dan maksimal.